Normal Radiographic Anatomy of the Donkey Foot from Birth to 2 Years of Age. (September 2015) - Van Thielen, B.; Pestieau, P.; Van Der Strieckt, A.; Willekens, I.; Busoni, V.; Verhelle, F.; Goossens, P.; Delperdange, P.; De Mol, G.; Jacqmot, O.; Buls, N.; Kichou, M.; et al.
Abstract : Reasons for performing study: Normal radiographic anatomy of the juvenile donkey foot has not been reported previously. Objectives: To provide a radiographic survey of the anatomical development of the donkey foot from 0 to 2 years of age. Study design: Radiographic survey. Methods: The right front foot of 9 donkey foals born in the spring of 2012, housed and fed in the same conditions, were radiographed every month for the first 6 months of age and every 3 months for the following 18 months. Latero‐medial radiographs with and without barium markers at the coronary band and anterior‐posterior radiographs of both front feet were obtained during weightbearing. Radiographs were obtained at 55 kV and 3 mAs with mobile x‐ray equipment (Gierth RHF 200 ML, Examion DR810). Results: The distal physis of the metacarpus (McIII) was closed at the mean age of 17.8 months (SD: 11.5, 21). The proximal physis of the proximal phalanx was closed at the mean age of 15.5 months (SD: 11.5, 21). The distal physis appeared as a clear radiolucent line at 2 weeks of age and was still visible subtly at 24 months. The proximal physis of the middle phalanx was closed at the mean age of 10.7 months (SD: 11.5, 19). The distal physis was visible at birth but closed at 4 days. Conclusions: Based on our results, it seems that physes close at an older age in the donkey foal than in the horse. Ethical animal research:  The study was approved by the Ethics committee of the Vrije Universiteit Brussel (VUB), Brussels, Belgium. (VUB/14‐272‐2). Owners gave informed consent for their horses' inclusion in the study.Source of funding:  The authors acknowledge Vtrade Belgium for the logistic assistance.Competing interests:  None declared.